(3eSJTGQ GdCef Gdbhei MGaX ESeGYjds (3aNQ GdYScQjI hGdOHdheGSjI GdeUQjIs - (3YWjI, QLGFis ((3GdbGgQIs (3OGQ GdgdGds, 2015)
(3de jcf ai JNWjWi, Mjf HOCJ cJGHI gPg GdSWhQ hfTQgG cd CMO HLQjOI GdeGd bHd CcKQ ef YGejf, Cf CSJQSd dhVY cJGH gh (B_ (3egeG HPd ajg (B_ (3jbUQ Yf GdEMGWI HLhGfH gPG GdYXje, UGMH GdebGe GdQajY MGaX ESeGYjd (B. (3HjO Cf JGQjN hSjQI hCYeGd gPg GdbGeI GdYRjRI GdbGOQI, bO aQV faSg, heVjJ heVi Gdbde eYi ai GSJQSGd aQVg fgQ OGab dG jJhba, hLOJ eOOg (B_ (3HdG JNWjW (B- (3TGNUkG CeGei jOYhfi ddGSJWQGO, adHjJ hGSJWQOJ, acGf gPG GdcJGH GdPi CbQ Cfg Ohf eG jSJMbg gPg GdbGeI GdJi GMJdJ ecGfI SGebI ai JGQjN GdhWf, hdOi GdYGQajfs
1 16
Keywords: (3GdOHdheGSjhf GdeUQjhfs; (3GdedMbhf GdSjGSjhfs